Discourse markers in diplomatic setting: Ministerial dialogue between Australia and Indonesia - Rosaria Mita Amalia; Elvi Citraresmana; Nurul Hikmayaty Saefullah (Studies in English Language and Education, 2021)
This descriptive research discusses the use of discourse markers in a diplomatic setting between the governments of Indonesia and Australia during a Joint Press Conference between Indonesia-Australia Foreign and Defence Ministers. The particular aims of this research are to identify and analyze forms of discourse markers employed by the representatives of each government and describe the most frequent discourse markers used by these representatives. The data were collected from the transcript of the Joint Press Conference between Indonesia and Australia Foreign and Defence Ministers (2+2) Dialogue. The data are classified based on the typology of discourse markers and analyzed to identify their function within the diplomatic discourse. The data are input into the AntConc corpus analysis toolkit for analysis. The results show that the Foreign and Defence Ministers of Indonesia employed three forms of discourse markers, namely textual discourse marker, interpersonal discourse marker, and cognitive discourse marker, whereas the Foreign and Defence Ministers of Australia only applied textual discourse marker and cognitive discourse marker. Both representatives employed textual discourse markers more frequently than other forms of discourse markers. Discourse markers partially control how meaning is constructed by showing turns between speakers, joining concepts, displaying attitude, and finally, controlling communication. By understanding the discourse markers in ministerial dialogues, spectators can learn to find clues in the change of direction in their talks to better understand the conversation that affects the policies and citizens of both countries involved.